Encountering Christ: Karl Barth and Mysticism - Holmes, Austin (Lumen et Vita, 2018)
By virtue of his insistence on the once and for all revelation of God in Jesus Christ, Karl Barth’s theology has sometimes been perceived as hostile to mysticism and contemplative spirituality. Allegedly, the significance of ongoing encounters with God is lost under the weight of the proclamation of Jesus Christ as the decisive moment of God’s dealing with humankind. A closer reading of Barth, however, reveals a different story. Interestingly, no serious survey of Barth’s thought on mysticism exists. This paper will seek to address this gap in scholarship by briefly exploring Barth’s relationship to mystical theology through engagement with his work, especially on 1) Union with God, 2) existentials of the theologians, and 3) Barth’s ecstatic socialism. Contrary to the general assumptions, Barthian theology represents an undeniably rich, and modern, mystic sensibility. Aside from challenging scholarly misrepresentations of Barth, the paper raises the question of how dogmatic theology and religious experience came to treated separately in the historical development of the church and theological scholarship.